Social Assistance by Corporations in Pandemic Era: Between Obligations or Culture? - Danang Wahyu Muhammad; Izzy Al Kautsar (International Journal of Social Science and Business, 2023)
Gotong royong is the cultural root of Indonesian society. The attitude of gotong royong is manifested in togetherness and kinship as integration of Indonesian people. The Pandemic of the new coronavirus has extensively tested the course of gotong royong values. In the context of corporate’s philanthropy activities, it aims to provide social benefits, the current trend shows there is a new corporate philanthropy paradigm, namely strategic philanthropy that can provide social benefits while increasing long-term profits such as spread the existence of the product name, and foster partnerships between business units. This study analyze the trends, motives, and moral directions of the corporate's philanthropic activities after introducing pandemic restrictions on national culture (gotong royong). The research method used in this research is normative with a conceptual approach. This study uses secondary data through primary legal materials and secondary legal materials. The data collected will be analyzed using a qualitative approach and stated descriptively. The final results of those research that there are a considerable effect of corporate morality strongly influences the motives and motivation of corporations in carrying out social activities. Corporate morale is influenced by stakeholder backgrounds, goals, and corporates business strategies. So in order to maintain the unity and stability of the corporations and the surrounding community, multi-stakeholder collaboration with the principle of gotong royong through national clusters to overcome the impact of the COVID-19 Pandemic is urgently needed.